Pneumomediastinum secondary to mephedrone inhalation. (7th June 2013) - McCullough, Chris; Keane, Margaret Geraldine; Hillman, Toby; Elkhodair, Samer
Abstract : A 23-year-old man presented to the emergency department with severe, central, pleuritic chest pain. The pain was present on waking and exacerbated by movement. On examination, supraclavicular and anterior chest wall surgical emphysema was noted, otherwise examination and initial observations were normal. A chest x-ray and subsequent chest CT demonstrated a pneumomediastium with significant subcutaneous emphysema. There was no history of vomiting or chest trauma, but the patient had inhaled mephedrone, a synthetic stimulant drug, 36 h prior. Pneumomediastinum is an uncommon complication of inhalational drug use.